Guía gastronómica del cantón Salcedo de la provincia de Cotopaxi. - Ramos Chicaiza, Tiffany Alexa (2021)
This study focuses on the gastronomy of the Salcedo canton since this is part of its traditions and cultural identity that over the years the preparation of its representative dishes has been changing and adapting to current life. The research has a qualitative methodological approach since complete data is collected on the issue raised in order to achieve an interpretation of the results based on the cultural or ideological aspects of the study area. The first part of the project focused on the gathering of primary and secondary information through the bibliographic review of books and virtual documents where the current situation of the study area was analyzed taking into account three aspects: the economic, socioeconomic and environmental aspect, in this way it was determined that the Salcedo canton is divided into 6 parishes, 1 urban and 5 rural, in which its main source of economic income is livestock and agriculture. In the second phase, several field trips were carried out to obtain an inventory of the intangible cultural heritage applying the INPC files to know the number of representative dishes of the Salcedo canton, resulting in a total of 16 representative manifestations of the place, of which 12 They belong to the daily gastronomy and the four remaining dishes are of the festive type. To meet the third objective, a descriptive gastronomic guide of the Salcedo canton was developed using the data and information from the inventory systematization, which can be used as a means of disseminating the gastronomic heritage. In conclusion, Salcedo is a place that has a variety of gastronomy and with good conditions to develop tourist activities that allow the development of the site. It is recommended that the authorities carry out more cultural and gastronomic projects so that people value the knowledge that frames the history of the place and thus does not get lost in time.